Keluhan Subyektif Gangguan Pernafasan Pada Pekerja di Area Stockpile Batubara Jambi - Fauziah, Ana; Budiyono, Budiyono; Raharjo, Mursid (Jurnal Ilmiah Mahasiswa, 2020)
Coal operations can produce dust. Coal dust that can be solved by breathing in workers. The results of observations of loading and unloading activities, coal transport trucks causing dust to fly. Dusty work areas can be seen from the surrounding plants blackened, as well as the workerâ€™s limbs due to coal dust attached. The results of measurement of air quality in the work environment are known to be below the NAV in accordance with Permenakertrans No. 5 of 2018. The purpose of this study was to discuss the relationship of coal dust exposure with subjective complaints of respiratory disorders at coal stockpile workers. This study was an observational study with a cross sectional design with a total sample of 36 workers. Data collection by measuring PM 2.5 in ambientÂ  with EPAM 5000 Haz-Dust, measurement of respirable dust levels with Personal Dust Sampler (PDS), Knowing nutritional status through body mass index (BMI) and worker data and subjective complaint respiratory disorders with the questionnaire. Univariate data analysis and bivariate with the chi-square test. The results showed that 83.3% of workers with respirable coal dust exposure were higher than the threshold value (NAV) and 63.9% of workers who discussed subjectively breathing problems. The conclusion from this study there is relationship between the use of PPE (mask) obtained p-value = 0.006 and smoking habits (p = 0.005) with subjective complaint of respiratory disorders on workers in the coal stockpile.